1990
DOI: 10.5980/jpnjurol1989.81.1680
|View full text |Cite
|
Sign up to set email alerts
|

Urinary FDP D-Dimer and E Fragments in Renal Transplantation

Abstract: Both D-dimer and E fragments in urinary FDP were determined in renal transplantation patients. Urinary D-dimer fragments increased in 14 out of 20 acute rejections (70.0%) and in 6 out of 18 chronic rejections (33.3%). Urinary E fragments increased in 8 out of 9 acute rejections (88.9%) and in 4 out of 5 chronic rejections (80.0%). It is suggested that urinary FDP-E fragment is a better indicator to detect or predict rejection than the whole Urinary FDP. The appearance of D-dimer in the urine indicates intrava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
1993
1993

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…PIC is a complex of cb-plasmin inhibitor and plasmin. cb-Plasmin inhibitor, which has the capacity to adjust the fibrinolytic system of the body, can instantly and irreversibly link to plasmin to form an important sub stance to maintain and adjust the dissolving of a throm bus [10], PIC reflects plasmin production through the inactivation of plasminogen, and can be used as an impor tant index of acceleration of various fibrinolytic functions [11], D-D is a fraction of the degradation product formed only through the secondary fibrinogenolysis of stabilized fibrin, and FDP is a degradation product of fibrin and fibrinogen [12], In ESWL for renal stones, elevation of the blood level of TAT occurred on the 1st postoperative day and eleva tion of the blood level of PIC occurred on the 3rd postop erative day. Studies on blood levels of TAT and PIC after partial hepatectomy revealed that the elevation of TAT reached a peak between immediately and 1 day after the operation, PIC, on the other hand, between 3 and 5 days after the operation [13].…”
Section: Methodsmentioning
confidence: 99%
“…PIC is a complex of cb-plasmin inhibitor and plasmin. cb-Plasmin inhibitor, which has the capacity to adjust the fibrinolytic system of the body, can instantly and irreversibly link to plasmin to form an important sub stance to maintain and adjust the dissolving of a throm bus [10], PIC reflects plasmin production through the inactivation of plasminogen, and can be used as an impor tant index of acceleration of various fibrinolytic functions [11], D-D is a fraction of the degradation product formed only through the secondary fibrinogenolysis of stabilized fibrin, and FDP is a degradation product of fibrin and fibrinogen [12], In ESWL for renal stones, elevation of the blood level of TAT occurred on the 1st postoperative day and eleva tion of the blood level of PIC occurred on the 3rd postop erative day. Studies on blood levels of TAT and PIC after partial hepatectomy revealed that the elevation of TAT reached a peak between immediately and 1 day after the operation, PIC, on the other hand, between 3 and 5 days after the operation [13].…”
Section: Methodsmentioning
confidence: 99%